Pengaruh Budaya Organisasi dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Arudam Sejahtera di Pamekasan - Rahayu, Runik Puji; Djaja, Moh Herman (Assyarikah: Journal of Islamic Economic Business, 2024)
This study was conducted to observe the impact of the influence of organizational culture and work motivation on employee performance which is an important issue in a number of organizations. This research is an explanatory study, where researchers make observations in collecting research data and recording data as it is, analyzing and explaining the data. The research took place at PT. Arudam Sejahtera Pamekasan by taking the population on employees as a whole. This is based on the total number of employees which only reaches 105 people. So that the sampling in this study was carried out randomly and the size of the sample taken amounted to 82 respondents. The purpose of this study is to determine the significant influence of organizational culture and motivation on employee performance at PT. Arudam Sejahtera Pamekasan partially. And to know organizational culture and motivation have a significant influence on employee performance. Overall, this study can be concluded that independent variables have a significant influence on employee performance simultaneously and partially.